Caracterização de pacientes e de dietas enterais artesanais de centros de alta complexidade em oncologia quanto aos teores de poliaminas - Cyntia Karine Barreto Batista (2007)
CARACTERIZATION OF PATIENTS AND OF ENTERAL HOMEMADE DIETS FROM CENTERS OF HIGH COMPLEXITY IN ONCOLOGY WITH RESPECT TO POLYAMINES. The five Centers of High Complexity in Oncology (CACON) from Belo Horizonte, MG were included in this study. Questionnaires were filled out by the person in charge regarding the homemade enteral diets prescribed to patients under cancer treatment after hospital discharge and also regarding information on the manipulation of the diets. The levels of bioactive amines in ingredients of the diets were determined. The contents of calories, protein, vitamin A, calcium, iron and bioactive amines of the diets were calculated and compared to recommended values. Cancer of the head, neck and of the digestive tract in male patients were the most prevalent and the mean age was 59. The homemade enteral diet was prescribed by every CACON. The diets from only one CACON did not reach the prescribed caloric content. 100% of the CACON reached the recommended protein intake for women and 40% for men. 40% of the CACON reached the recommendations for calcium and vitamin A for women and 60% for iron and vitamin A for men. In one of the CACON, the levels of vitamin A exceeded the tolerable maximum value. The polyamines spermine and spermidine were detected in 69 and 48% of the ingredients, respectively. The most relevant sources of spermine were the meats and beans. With respect to the other amines, putrescine was detected in 32%, agmatine and histamine in 20%, cadaverine in 12%, and tyramine, phenylethylamine and tryptamine in 8% of the ingredients analyzed. Serotonin was detected only in orange. These amines were present at low mean levels ( 0,71 mg/100 g) except for putrescine in orange (4,69 mg/100 g) and phenylethylamine in pumpkin (1,98 mg/100 g). The levels of polyamines were higher in diets from CACON C, followed by B. The diets from CACON A were the ones with lower levels of polyamines and of the other bioactive amines.